Fundamental studies of milk exosomes Camelus dromedarius, Camelus bactrianus and hybrids from Kazakhstan (Experimental biology, 2020)
Milk contains extracellular vesicles that are released by udder cells and are recognized as a new mechanism for transmitting information from mother to newborn. In this study, extracellular vesicles were isolated from milk of C. dromedarius, C. bactrianus and hybrids from Kazakhstan using optimized density gradient ultracentrifugation. Vesicles were visualized using transmission electron microscopy and characterized using nanoparticle tracking analysis. The purified extracellular vesicles had a heterogeneous size distribution ranging from 25 to 170 nm in diameter with an average yield of 9.5*108 – 4.2*1010 particles per milliliter of milk. Combining classical and advanced proteomic approaches, a comprehensive proteomic analysis of camel milk vesicles was carried out. One thousand ten (1010) unique proteins have been identified that are involved in various biological processes, including most markers associated with small vesicles. As a result, the extracellular vesicles of camel milk are enriched with exosomal proteins. The most common biological processes have been associated with the synthesis and secretion of exosomes. They are mainly involved in molecular functions such as poly RNA and ATP binding, protein binding and structural constituent of the ribosomes.Key words: camel milk, exosomes, extracellular vesicles, proteome.